Answer: V = √gh
Explanation: This question can be solved by considering conservation energy.
Also we need to take the moment of inertia of the two bodies into consideration.
Total kinetic energy consists of transla-tional and rotational kinetic energies. Non slipping means v=rω and for the ring I=M R^2. The ring has kinetic energy due to transla-tional and rotational velocity.
Therefore:
mgh = (1/2 m V^2) + (1/2 . I w^2)
mgh = (1/2 . m . V^2) + (1/2 m R^2 . V^2/ R^2)
gh = V^2
the velocity vring of the ring when it reaches the bottom will be:
V = √gh